Analisis Intensitas Kebisingan pada Lingkungan Kerja Area Tambang Bawah Tanah Berdasarkan Permenaker Nomor 05 Tahun 2018 - Erita Shintia (Fakultas Teknik, 2024)
Noise is a sound that has an intensity above the safe threshold and can interfere with the health of people exposed to it, causing a decrease in work productivity. This research location is in one of the underground mines that is still in the development stage, in which there are several drilling work areas for rock sampling. These activities produce considerable noise, so it is necessary to analyze the noise level. This study aims to determine the intensity of noise in the drilling work area and compare it with the quality standard based on Permenaker Number 5 of 2018, and to determine the distribution of noise intensity with the surfer program so that noise mapping can be produced. Data collection locations are located in 6 drilling work areas. This study uses a simple method of taking noise level data using a Sound Level Meter (SLM) tool with several time variations, namely 5, 10 and 15 minutes. The noise intensity data was then mapped using Surfer 13 software. The intensity data was also used to determine the level of reduction after wearing ear protection equipment. The results of taking noise intensity data with time variation show that there is no significant difference. The coefficient of variation of the time variation during data collection is less than 1%. The average noise intensity in the 6 drilling areas is 88.5 - 91.3 dBA. The ear protection equipment used by the company is an earplug that can reduce noise by 13 dBA. The noise intensity value in the underground mine drilling area is above the threshold value based on Permenaker Number 5 of 2018 which is 85 dBA. The company can optimize supervision of the use and maintenance of ear protective equipment for workers so that it can effectively reduce the noise exposure received.
Reuploud Repository hasyim Mei 2026 Validasi file repositori 26 Mei 2026_(Vivi)_Firli
Keywords: underground; noise; time interval; threshold limit value